The European Commission and Europe's Democratic Process - Brown, Stuart A. author. aut Link
V, 112 p.
Keywords: This book examines the multitude of challenges which the European Commission faces: once the centre of political gravity in Europe’s integration process, the growth of Euroscepticism and the emergence of new institutional rivals threaten to undermine its status as an institution. Tracing the roots of the Commission’s decline from the early 1990s through to the Eurozone and refugee crises, Stuart A Brown draws on new evidence to illustrate why the EU’s executive now faces a battle for its future, and asks whether in the reforms of Jean-Claude Juncker the Commission may be facing its last chance. This study will appeal to students and scholars in EU institutions, politics, and public policy.